2016
DOI: 10.1159/000446968
|View full text |Cite
|
Sign up to set email alerts
|

Standardized Grading of Shock Wave Lithotripsy Complications with Modified Clavien System

Abstract: Introduction: Definitive consensus on grading of complications of shock wave lithotripsy (SWL) does not exist. The objective of this study was to grade complications of SWL in relation to different stone and shock wave parameters, according to the modified Clavien system. Materials and Methods: Complications observed in 2,648 patients who underwent SWL between January 2003 and May 2014 were evaluated statistically and stratified into 5 grades by the modified Clavien system focusing on stone and shock wave para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…Sepsis after SWL is higher in patients with untreated UTIs or in those who present with infected stones. A previous study mentioned that the incidence of low‐grade fever after SWL was 19.4% of patients, which was conservatively managed in the majority of cases [23]. In our study the incidence of post‐SWL fever was 3% in the narrow‐focus group and 2.9% in the wide‐focus group.…”
Section: Discussionsupporting
confidence: 46%
“…Sepsis after SWL is higher in patients with untreated UTIs or in those who present with infected stones. A previous study mentioned that the incidence of low‐grade fever after SWL was 19.4% of patients, which was conservatively managed in the majority of cases [23]. In our study the incidence of post‐SWL fever was 3% in the narrow‐focus group and 2.9% in the wide‐focus group.…”
Section: Discussionsupporting
confidence: 46%
“…Extracor- [1,8] . Meanwhile, Mittal et al [9] suggested the use of Modified Clavien System in adults for determining SWL complication rates and standardizing procedural errors. In contrast to adult studies, studies with children reporting the effects of urinary catheterization during SWL with nephrolithiasis are rare.…”
Section: Discussionmentioning
confidence: 99%
“…All radiographic images were evaluated by the same radiologist and urologist to minimize interobserver variability. Clavien-Dindo classification was used in the evaluation of complications [15].…”
Section: Methodsmentioning
confidence: 99%